Collection of Literary Ecological Poetry "Works of Biology Education Students" Overview of Physical Intrinsic Elements - Yulian Dinihari; Mashudi Alamsyah; Tantry Aghnitya Sari (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Good poetry is poetry that contains intrinsic elements in it. The more fulfilled these intrinsic elements, the more meaningful the content in it will be. Ecolinguistics is one of the studies in linguistics that connects ecosystems with language that is part of human life (ecology). Literature in this poetry-making activity, students are expected to be able to improve their abilities in the field of poetry which tells them the connection between language and the study program they are taking, namely biology. The purpose of this study was to find out what are the physical intrinsic elements in a collection of literary ecology poems by first semester students, Biology Education, Indraprasta University PRGI. The research method used is descriptive qualitative by taking intrinsic elements from fictional elements consisting of diction, rhyme, typography, images, and language style. The data was collected by collecting the results of the student's literary ecology poetry, after the data was collected it was analyzed and described based on the table of physical elements. The results showed that from 28 collections of ecological poetry by students, there were physical intrinsic elements, namely diction, rhyme, typography, imagery, and language style. The most physical intrinsic elements in the collection of ecological poetry are style of language 28 or 31%, then the second most is diction or 28.6%, the third most is imagery as much as 25 or 27.4%, then rhyme 9 or 9.8%, and the last is typography as much as 3 or 3.2%. Language style and diction are the most common in the physical intrinsic elements of a collection of ecological poetry by students.Keywords: Intrinsic element; Physical Elements; Ecology Poetry.